Analysis of Effect of Education Entrepreneurship and Family Environment Towards Interest Students Entrepreneurs - Periansya Periansya (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
This research aims to analyze the effect of entrepreneurship education and family environment on entrepreneurial interest. The population in this research is State Polytechnic of Sriwijaya Palembang student.. Sampling technique uses sampling proportional technique. Sample consists of 375 students. Analysis method uses double linear regression analysis technique. The result shows that partially entrepreneurship education, family environment gives a positive and significant effect on entrepreneurial interest of State Polytechnic of Sriwijaya. Simultaneously, entrepreneurship education and family environment gives a positive and significant effect on entrepreneurial interest.. The conclusions in this research that the education needs to be orientating on practice, case study, and invite interviewees from companies or industries. The existence of industrial practice based on student competency also can enhance knowledge and insight of students where